Synergy between surfactants’ stiffness and concentration on their self-assembly into reverse micelles as water droplet carriers in nonpolar solvents - Hernández Velázquez, J.D.; Gama Goicochea, A. (PloS one, 2024)
A study of the self-assembly process into reverse micelles (RMs) of linear surfactants and monomeric aqueous solutes dissolved in nonpolar solvents, varying the concentration ( c s ) and the persistence length ( L p ) of the surfactants is presented here. The influence of c s and L p on the structural and dynamic properties of the aggregates is investigated through mesoscopic simulations carried out with the dissipative particle dynamics method. All simulations are performed at a fixed water/surfactant molecular ratio of 2:1, varying the surfactant concentration from c = 6 wt % up to c = 12 wt %, for increasing surfactants’ rigidity from L p = 0.73 nm up to L p = 44.99 nm. It is found that there exists a collaborative interplay between c s and L p that enhances the number of RMs assembled and their diffusion as carriers of water droplets. These results should be useful as guidelines to understand and improve processes where the RMs are implemented to carry aqueous solutes in nonpolar solvents.